دور التحليل المالي و مراقبة تسيير المؤسسات الاقتصادية - بن يوسة, صباح (My University, 2020)
This study aims to know the role of financial analysis in the monitoring of the economic establishment, by applying this on the union of agricultural cooperation for mostaganem, where various financial analysis tools where applied to the institution as well as their contribution to the assessment of financial performance and decision-making process Financial analysis is one of the most important modern management tools to monitor the financial statements and interpret the findings reached and discussed are its causes, with the aim of financial status of the foundation, and this is discovering the strengths and weaknesses of the foundation in the plans, fiscal policies, developing solutions and recommendations. Allows the goals.
مؤسسة إتحاد التعاونيات الفلاحية مستغانم
Keywords: Monitoring, financial analysis, financial statement, financial position